Architectural Design Methods According to Advance Human’s Intellect & Technology - Haddad, Ahmed Talib Hameed (Iraqi Journal of Architecture and Planning, 2018)
This paper explain design method as a ring or relationship link between theory and applied , and it discuss the important developments in the field of architectural design methods according to advance human’s intellect & his technology ; firstly from intuition thinking ( according to try and error ) to the industrial revolution that is followed mathematical and rational limitation thinking , and this thought go directly to un-limitation thinking thatâ€™s followed new scientific revolution , and it is arrive to contemporary digital revolution . Beside this that paper search for a development relationship between architectural form and architectural design methods . Finally must be recommendation how to effect this important development in design methods and tools on the task of teach architectural design.